Depth Function of Available Phosphorus and Potassium Distribution in Different Mid-Mesopotamian Plain Saline Soils - Kusay A. Wheib; Afrah K. Al-Jubouri; Husian A. Isa; Wejdan T. Kadhim (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
Saline soils in Alsweira greater area representing mid-Mesopotamian plain saline soils were selected to study the effect of salt accumulation on available potassium and phosphorus in soil as a depth function. Strip transect area representing sever salt affected areas was located and soil samples was chosen along that transect. Results showed that soil salinization phases in the area was Chloridic and sulphatic salinization, therefore it affected the salt distribution in soils. The most dominant salt compound was sodium chloride in Chloridic salinization soils, while sodium sulphate was the dominant salt compound in sulphatic salinization areas. Results showed that the content of available phosphorus was fairly low while available potassium showed different ranges in soil. Available potassium was significantly positive correlated to electrical conductivity (ECe) while available phosphorus was significantly negative correlated with ECe. These results were figured as depth functions of these available nutrients in soil where the highest content of available potassium was in the upper horizon decreasing with depth, while available phosphorus showed a significant decrease with depth as soil salinity decreases with depth.